Liverworts of Sphagnum magellanicum Brid. Raised bogs from Tierra del Fuego National Park, Ushuaia (Argentina) - Souto, Martín (2015)
At present, the available information about the liverworts of Sphagnum magellanicum Brid. mires from South America is very limited. The main aim of this paper is to present a comprehensive study of the liverwort flora of this habitat, as well as details on the chorology and ecology of the taxa involved. Four different environmental units were examined, based on the water table level and plant cover, in three representative raised bogs from Tierra del Fuego National Park (Ushuaia). Floristic releve´s were recorded in 93 square plots (0.5060.50 m2 ), distributed at random in the environmental units. Twenty-four liverwort species have been identified; the majority have a Subantarctic distribution and there were a remarkable number of Magellanean endemics (11 species). Among the rare species, there were two new records for the Argentinian Province of Tierra del Fuego, Cephaloziella byssacea and Chiloscyphus notophyllus. The ecological preferences of the species were analysed based on their frequencies in the four environmental units examined. Only six species demonstrated significant correlation with some of the environmental units. Riccardia pallidevirens, R. georgiensis, R. alcicornis, and Cephaloziella varians, showed a preference for waterlogged and wet habitats, while Calypogeia sphagnicola and Cephalozia chilensis were linked to dense carpets of Sphagnum magellanicum.